THE INFLUENCE OF AQIDAH AKHLAK AND SOCIOLOGY LEARNING OUTCOMES ON THE FORMATION OF STUDENT CHARACTER - Eva Karlina Dwi Astuti; Tarsono Tarsono; Yani Suryani (Jurnal Tatsqif, 2020)
Abstract This study aims to determine the effect of moral theology learning outcomes and sociology learning outcomes on the formation of student character. This research uses a quantitative approach because the data presented is in the form of numbers. The method used is descriptive correlational. The research subjects were taken from 26th grade XI students. Data was collected using test, documentation and observation methods. Data were analyzed using IBM's SPSS version 26 application program. Hypothesis testing is done by statistical analysis techniques that are using multiple linear regression test. Based on the results of the study concluded that there is an influence of moral theology learning outcomes and sociology learning outcomes together can have an influence on student character. It is proven that the significance value of the regression in the ANOVA test table is 0,000 (<0.05), then Ho is rejected and H1 is accepted. The magnitude of influence is equal to 57.7%. Keywords: Learning outcomes; moral theology; Sociology; Character building.